The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9010125
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Two Dietary Approaches on the Quality of Life and Gastrointestinal Symptoms of Individuals with Irritable Bowel Syndrome

Abstract: To evaluate the effectiveness of a low FODMAP (fermentable oligosaccharides, monosaccharaides, disaccharides and polyols) diet in the relief of symptoms and an improvement of the quality of life in individuals with irritable bowel syndrome in comparison to a standard diet according to the British Dietetic Association’s guidelines. A non-randomized clinical trial of adult patients with IBS was compared two diet interventions. An assessment of symptoms, quality of life, and nutritional status was performed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Where no end values were reported, change from baseline data were used instead [ 41 , 42 ]. Where insufficient data were available to calculate or extract the mean and standard deviation, the study was excluded from analysis [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Where no end values were reported, change from baseline data were used instead [ 41 , 42 ]. Where insufficient data were available to calculate or extract the mean and standard deviation, the study was excluded from analysis [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding, these factors represented inevitable consequences of a long-term personalised diet, which introduced a daily lipid intake based on a typical Mediterranean diet. Guerreiro et al [ 44 ] reported that the “elimination phase” of a LFD leads to reduced body weight and BMI, following caloric restriction of some foods high in FODMAPs. Portion control is essential in a LFD, as larger portions can surpass safe thresholds, changing food from low to high FODMAP content [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the eligible studies (n = 9) had data on mean total FODMAP intake (strict phase; n = 7, modified phase; n = 2), 3,[5][6][7][8][9][10][11][12] with seven of the articles having data on mean fructan intake (strict phase; n = 5, modified phase; n = 2). 3,5,7,[9][10][11][12] Studies assessing fructan intake in healthy individuals were included for comparison (n = 2). 13,14 Total FODMAPs at baseline or in the control group ranged between 13.0-29.6 g/day, with total FODMAPs ranging between 3.1-22.0 g/day following the short-term phase (n = 7).…”
Section: To the Editormentioning
confidence: 99%
“…13,14 Total FODMAPs at baseline or in the control group ranged between 13.0-29.6 g/day, with total FODMAPs ranging between 3.1-22.0 g/day following the short-term phase (n = 7). [5][6][7][8][9][10][11] The total FODMAP intake reduction from baseline to the short term phase of the low FODMAP diet varied between 24% to 86% (Fig. 1).…”
Section: To the Editormentioning
confidence: 99%